1 Connecticut General Statutes: Revision of 1930, at 903 (1930) - (:unkn) unknown (My University, 1930)
Dealing in Explosives; License., ch. 147, § 2644: Dealing in Explosives; License., ch. 147, § 2644: Prohibited the manufacture, storage, sale, or dealing in gunpowder or any material defined as an explosive in § 2638
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER